Bridging the Linguistic Gap: Development of learning media for a Special Indonesian-Arabic Dictionary: Menjembatani Kesenjangan Linguistik: Pengembangan media pembelajaran Kamus Khusus Indonesia-Arab - Abdullah, Achmad Farouq; Rini, Fitri Setyo; Syarifah, Syarifah (Universitas Muhammadiyah Sidoarjo, 2024)
The necessity for dictionaries as a media for foreign language students, including Arabic, has consistently grown in significance. Particularly designed for students with a concentration in specialized disciplines, such as information engineering or technology. Nonetheless, an issue arises whereby pupils enrolled in the informatics engineering program at Darussalam Gontor University's Faculty of Science and Technology encounter challenges when attempting to compose scientific papers in Arabic due to the fact that, in addition to English, Arabic is required as the language of instruction for final assignments like theses. The issue is that there is no Indonesian-Arabic dictionary that could assist them in translating scientific terms into Arabic in accordance with their study program. At the moment, the Arabic-Indonesian dictionaries that are accessible are characterized by their general nature, lacking subject-specific specificity. Drawing from the provided information, the researcher intends to undertake an investigation concerning the compilation of the dictionary